Hidden in plain sight: America's slaves of the new millennium - Mehlman-Orozco, Kimberly (Praeger, an imprint of ABC-CLIO, LLC, 2017)
Prologue -- Part I. Sex trafficking -- Runaways, from the frying pan into the fire -- Happy beginnings, sad endings -- Disposable wives -- Child sex tourism -- Adult sex tourism -- Human trafficker deployment -- Trafficked to La Mara -- Now recruiting for an exciting summer abroad -- Mentality of a monger -- Part II. Labor trafficking -- Legal and still exploited -- Domestic servants, diplomatic slaves -- Knocking at your door -- Dark side of chocolate from the Cote d'Ivoire -- Slaved in India, retailed in America -- Cheap luxury -- Stealing our jobs? -- Part III. Overcoming barriers to the abolition of modern slavery -- Hidden in plain sight -- Disposable kids -- Whac-a-Mole crusade online -- Blaming the hotel -- Crimmigration and labor trafficking -- Out of the shadows -- Appendix A: Sex work terminology and abbreviations -- Appendix B: Sample human trafficking expert witness testimony outline -- Appendix C: Gathering data from human trafficking survivors -- Appendix D: Sample sex tourist timeline: Dirk -- Appendix E: Additional quotes from mongers -- Appendix F: Sample tool to identify youth at high-risk of being trafficked